High-performance semi-transparent perovskite solar cells with over 22% visible transparency: pushing the limit through MXene interface engineering - Yuan, Zhengtian (2023)
Semi-transparent perovskite solar cells (ST-PSCs) have attracted enormous attention recently due to their potential in building-integrated photovoltaic. To obtain adequate average visible transmittance (AVT), a thin perovskite is commonly employed in ST-PSCs. While the thinner perovskite layer has higher transparency, its light absorption efficiency is reduced, and the device shows lower power conversion efficiency (PCE). In this work, a combination of high-quality transparent conducting layers and surface engineering using 2D-MXene results in a superior PCE. In situ high-temperature X-ray diffraction provides direct evidence that the MXene interlayer retards the perovskite crystallization process and leads to larger perovskite grains with fewer grain boundaries, which are favorable for carrier transport. The interfacial carrier recombination is decreased due to fewer defects in the perovskite. Consequently, the current density of the devices with MXene increased significantly. Also, optimized indium tin oxide provides appreciable transparency and conductivity as the top electrode. The semi-transparent device with a PCE of 14.78% and AVT of over 26.7% (400-800 nm) was successfully obtained, outperforming most reported ST-PSCs. The unencapsulated device maintained 85.58% of its original efficiency after over 1000 h under ambient conditions. This work provides a new strategy to prepare high-efficiency ST-PSCs with remarkable AVT and extended stability.